Emotional Appeal as a Determinant of Effectiveness in English Advertising Texts: A Linguistic and Cognitive Analysis - Sattorov, Abboskhuja (Indonesia Academia Research Society, 2024)
This study examines the role of emotional appeal in determining the effectiveness of English advertising texts, focusing on its impact on consumer engagement and decision-making. A multidisciplinary framework incorporating linguistic, cognitive, and socio-cultural perspectives, the research seeks to uncover the mechanisms through which emotional appeals influence the perception of brand messages. A diverse corpus of advertising texts from the fashion, technology, and healthcare industries were analyzed using content analysis and discourse analysis techniques. The study focuses on linguistic devices, including metaphor, hyperbole, rhetorical questions, and emotional triggers like joy, fear, nostalgia, and aspiration. The findings reveal that emotional appeal functions as a stylistic element and a cognitive and cultural tool that enhances brand recall, loyalty, and consumer engagement. Specifically, advertisements utilizing positive emotional triggers, such as humor and joy, resonate more deeply with audiences. In contrast, negative appeals, such as fear and guilt, are more effective in prompting immediate consumer action. The study highlights the importance of aligning emotional content with linguistic precision to optimize the persuasive impact of advertising texts. These results offer valuable insights for advertisers and contribute to the fields of advertising linguistics, consumer psychology, and persuasive communication, providing practical recommendations for developing more effective, targeted advertising strategies.